Intracellular chloride and hydrogen ion dynamics in the nervous system - Raimondo, J (2012)
Synaptic transmission in the nervous system involves the activation of receptor proteins that permit rapid transmembrane fluxes of ions. Ionic gradients across the membrane determine the direction and driving force for the flow of ions and are therefore crucial in setting the properties of synaptic transmission. These ionic gradients are established by a variety of mechanisms, including pump and transporter proteins. However, the gradients can be affected by periods of neural activity, which in turn, are predicted to influence the properties of ongoing synaptic transmission. In this thesis I have examined the concentration gradients of two ions that play a fundamental role in synaptic transmission: chloride ions (Cl-) and protons (H+). Type A γ-Aminobutyric acid receptors (GABAARs) are primarily permeable to Cl- and mediate the majority of fast post-synaptic inhibition in the brain. The transmembrane concentration gradient for Cl- is therefore a critical parameter in governing the strength of synaptic inhibition. In the first part of the Thesis I use a combination of experimental and theoretical approaches to demonstrate that influxes of Cl- via activated GABAARs can overwhelm a neurons ability to maintain a stable Cl- concentration gradient. The consequence is that subsequent activation of GABAARs results in weaker inhibition or even excitation, which alters how the neuron integrates synaptic inputs. This process is shown to be dependent upon the level of activity of the GABAAR, the post-synaptic cells membrane potential and the cellular compartment into which the Cl- flows. These principles were extended to demonstrate that popular optogenetic strategies for silencing neural activity have different effects upon GABAAR transmission. A light-activated Cl- pump was shown to cause substantial accumulations in intracellular Cl, which meant that the strength of synaptic inhibition was significantly reduced following light offset. In the second part of the Thesis I use electrophysiological and fluorescence imaging techniques to demonstrate that the activation of GABAARs during epileptiform activity results in pronounced changes to the transmembrane Cl- gradient. Indeed, these changes convert synaptic inhibition into synaptic excitation during the course of a seizure event. As part of this work I characterise a novel, genetically-encoded reporter for measuring intracellular Cl- dynamics in different cell types and subcellular compartments. A significant advantage of this reporter is that it permits the simultaneous quantification of H+ fluxes, which are also shown to change in an activity-dependent manner and which have been a confounding factor for previous Cl- reporters. In the third and final part of the Thesis I use genetically-encoded reporters to investigate activity-dependent changes in intracellular H+ concentration. I demonstrate that markedly different pH changes occur in neurons and astrocytes during epileptiform activity. Whereas neurons become acidic, astrocytes become alkaline and the dynamics of these pH shifts exhibit a very different temporal relationship with the seizure event. In conclusion, this thesis demonstrates that the intracellular concentrations of Cl- and H+ are dynamic variables that evolve across time and space, in an activity-dependent manner. Changes in the transmembrane gradients of these two ions influence ongoing synaptic transmission. Therefore this work has significant implications for our understanding of network activity and the balance of synaptic excitation and inhibition.